Interrelation Between Fibroblasts and T Cells in Fibrosing Interstitial Lung Diseases - Lai, Yunxin; Wei, Xinru; Ye, Ting; Hang, Lilin; Mou, Ling; Su, Jin (Frontiers in Immunology, 2021)
Interstitial lung diseases (ILDs) are a heterogeneous group of diseases characterized by varying degrees of inflammation and fibrosis of the pulmonary interstitium. The interrelations between multiple immune cells and stromal cells participate in the pathogenesis of ILDs. T cells are major mediators of adaptive immunity, as well as inflammation and tissue destruction in ILDs; while fibroblasts contribute to the development of ILDs through secreting extracellular matrix and proinflammatory cytokines upon activation. The interrelation between T cells and fibroblasts is vital for the immune processes in lymphoid organs such as lymph node and thymus. However, more and more evidences reveal that fibroblasts play important roles in modulating T cell recruitment, differentiation and function in multiple inflammatory conditions. Conversely, T cells can reshape the fibroblasts-orchestrated vessel system in lymphoid organs, tumors and fibrotic sites. A more precise understanding of interrelation between fibroblasts and T cells could enable a better future therapeutic design by targeting this interrelationship. Here we highlight recent work on the interplay between fibroblasts and T cells in health, infection, cancer and ILDs, and consider how distinct tissue or cellular contexts may alter the effects of the interaction between fibroblasts and T cells on tissue remodeling and how this contributes to beneficial or detrimental outcomes in ILDs.